ANALISA PERBEDAAN KINERJA KEUANGAN (LEVERAGE RATIO) PADA PERUSAHAAN PARTISIPAN INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) 2009-2011 - Vindy Tantyo (Business Accounting Review, 2014)
This study aimed to determine the differences of the company's financial performance (leverage ratio) that participated within ISRA during the period of 2009-2011. This study used total debt ratio, debt to equity ratio dan long term debt ratio as proxy of leverage ratio.The sample consisted of 26 public companies that participating in Indonesia Sustainability Reporting Award (ISRA) 2009-2011. The data of the study processed by using One way Anova and independent t test method. The result of the study showed that there was no difference in financial performance (leverage ratio) in participating companies in ISRA 2009-2011, but there was a difference in total debt ratio on company’s sector, and there were differences in those proxies of leverage ratio from the side of the company size.